Fences Booking System on True CV.Prima withMicrosoft Visual Basic 6.0 - Koesdwiyanto Wibowo (Jurnal Manajemen Informatika, 2010)
The development of increasingly sophisticated computers are very helpful in data processing still usingmanual systems. This often creates problems relating to the accuracy of the data resulted in delays indata processing.Information that is valuable information quickly and accurately. So needed a computerized system as asupporter. Rail reservation system in CV. True excellence is designed with the aim to obtain and processinformation quickly and accurately as well as secure data storage. So with the end result is useful indecision making.